The Effect Of Simple Drip Irrigation Using Plastic Bottles On Cocoa Plant Productivity In The Field Laboratory Service Garden - Neang, Maria Clotilde; Beja, Hendrikus Darwin; Wahyuni, Yuyun (PUCUK : Jurnal Ilmu Tanaman, 2024)
Cocoa plants (Theobrama Cacao L.) are one of the plantation commodities that play an important role in the indonesian economy. The need for sufficient water during the growing period is very important to ensure the vegetative and generative growth of plants, so that they can produce fruit with good quality. However, the availability of water in plantation areas is often a problem, especially in the dry season or in areas with uncertain rainfall such as in Maumere wich is currently experiencing a hot climate. This study aims to analyze the effect of simple drip irrigation using plastic bottles on cocoa plant productivity. The research was conducted at the Sikka Field Laboratory Service Garden for three months, from September to December 2024. The research method used a Randomized Block Design (RAK) with five treatments and four repetitions. The observed parameter is the number of flowers and cocoa fruit. The main material used is used plastic bottles asirrigation tools. simple, with small holes to distribute water direcly to the root zone. The results showed that treatment P3 (24 liters per week) produced the highest productivity, wich was an average of 318.25 flowers and an average of 16.5 fruits. The conclusion of this study is that simple drip irrigation using plastic bottles is an effective and efficient method to increase cocoa plant productivity, especially in areas with limited water resources. This method is environmentally friendly, easy to implement, and can be an innovative alternative to overcome conventional irrigation constraints.